Fixed-Point Theorems and Common Fixed-Point Theorems on Spaces Equipped With Vector-Valued Metrics - Hosseinzadeh, H.; Jabbari, A.; Razani, A. (Український математичний журнал, 2013)
We show the existence of fixed points and common fixed points for single-valued generalized contractions on the spaces equipped with vector-valued metrics. Показано існування нерухомої точки та спільної нерухомої точки для однозначних узагальнених стискувальних відображень на просторах із векторнозначною метрикою.